"Dry Mouth" From the Perspective of Traditional Persian Medicine and Comparison with Current Management. (April 2015) - Heydarirad, Ghazaleh; Choopani, Rasool
Xerostomia is a common problem, particularly in an elderly population, with a range of causes that affect important aspects of life, such as chewing, swallowing, and speaking. Xerostomia has been explained in traditional medicine throughout history. Traditional Persian medicine, with more than 4000 years of history, consists of the sum total of all the knowledge and practices used in diagnosis, prevention, and exclusion in Iran from ancient times to the present. Based on leading Persian medical manuscripts, the current study focuses on the medieval concept of xerostomia as an important general disorder to review the aetiology of xerostomia and xerostomia types, the control and treatment of xerostomia by lifestyle modification, and medicinal plants for xerostomia suppression according to the theory and practice of traditional Persian medicine. Xerostomia was treated with 3 major approaches in traditional Persian medicine: lifestyle modification, simple single herbal remedies, and compound medicines. It appears that all the factors that cause xerostomia in current studies can be described by using the theories of traditional Persian medicine; furthermore, therapies aimed at both medicines (current and traditional) focus on protecting salivary glands and salivary flow. As a conclution while current managements of xerostomia are still inadequate and traditional approaches have found experimental support over the centuries, some of these traditional treatments may still be useful to current medicine as alternative medicine.